EXPLORING THE PRESENCE OF GENDER STEREOTYPES IN THE FAMILY AND THEIR INFLUENCE ON CHILD DEVELOPMENT - Axnazarova Diyora Erkin qizi pfn. (PhD) (Journals Park Publishing, 2024)
This scientific article delves into the presence of gender stereotypes within the family context and examines their potential benefits in raising children. Gender stereotypes are deeply ingrained societal beliefs about the roles, behaviors, and characteristics associated with males and females. While gender stereotypes have been criticized for perpetuating inequality and limiting individual potential, this article explores the notion that certain aspects of gender stereotypes may provide a framework for children's socialization, identity formation, and understanding of societal norms. By understanding the nuances and potential benefits of gender stereotypes, parents and caregivers can navigate their impact more consciously, promoting healthy gender development while challenging harmful biases.
Keywords: Gender stereotypes, family, child development, socialization, identity formation, societal norms, benefits, framework, self-concept, exploration, autonomy